Aplikasi Kriptografi Menggunakan Algoritma Aes-128 (Advanced Encryption Standard -128) Berbasis Web Pada Laboratorium Ict Terpadu Universitas Budi Luhur - Diana Permatasari; Safitri Juanita (KILAT, 2016)
Document exam for midterm and final exam is one of the very important document because it is used by lecturers to evaluate the lecture material for Teaching and Learning Activities. ICT Laboratory Integrated Budi Luhur University as one of the operator of the test lab at the University of Budi Luhur who has responsibility for securing documents exams during the process of mid term and final exam, so in practice there is requiring an application to security documents such as Cryptography Web Based Application using algorithms AES-128 on Lab ICT Integrated Budi Luhur University. Method that is used to develop this application is using Waterfall model, this application used PHP with MySQL database. The research objective is to implement the algorithm AES-128 to encrypt and decrypt files exam on Lab ICT Integrated Budi Luhur University, securing document exam file that can not be read by anyone other than the owner of the file and the person who has access to the file. The conclusion of this study prove that the method algorithm AES-128 algorithm is excellent in secure files, as well as by the application of safeguards files, documents exams more awake, and confidential and the decryption process, the results of the file content decryption did not change from the original file.